A educação ambiental para além da legislação: uma perspectiva sobre o Ensino de História e Natureza - VALE, Blenda Carvalho do (2018)
The purpose of this article is to present an analysis of the difficulties of insertion of environmental education in the school context, foreseen on the aegis of the legislation that deals with this theme, with emphasis on formal education and history teaching. Analyzing its obligatoriness in all levels of education, as well as, stating how the teaching of History, more precisely the environmental history, is made of paramount importance for the realization of this right. Since the environmental debate brought by history helps to initiate the process of building a sustainable awareness in the student, and the perception of this as one of the main agents in the historical process.